Berettyóújfal u-Szilhalom, Ungarn: Soziale Transformationen und frühe Metalle – Forschungen zu Neolithikum und Kupferzeit in der Großen Ungarischen Tiefebene - Neumann, Daniel (e-Forschungsberichte des DAI, 2023)
Between 2013 and 2014 research was conducted on the settlement organisation and past landscape of the Neolithic and Copper Age on the Great Hungarian Plain. The main objective was a diachronic examination of the small tell like settlement Berettyóújfalu-Szilhalom and its environs. In the framework of this research different methods were applied to evaluate the archaeological potential of the site and develop perspectives for further research. The preliminary results of this assessment are presented here.